2013
DOI: 10.1002/ece3.902
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in chemosensation: lessons from an island nematode

Abstract: All organisms must interact with their environment, responding in behavioral, chemical, and other ways to various stimuli throughout their life cycles. Characterizing traits that directly represent an organism's ability to sense and react to their environment provides useful insight into the evolution of life-history strategies. One such trait for the nematode Pristionchus pacificus, chemosensation, is involved in navigation to beetle hosts. Essential for the survival of the nematode, chemosensory behavior may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…; McGaughran et al . ), we expected most Los Angeles isolates to exhibit weak attraction to the oriental beetle pheromone. We found that only a single one of 12 Cyclocephala ‐derived strains exhibited attraction to the oriental beetle pheromone (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; McGaughran et al . ), we expected most Los Angeles isolates to exhibit weak attraction to the oriental beetle pheromone. We found that only a single one of 12 Cyclocephala ‐derived strains exhibited attraction to the oriental beetle pheromone (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Studies on La Réunion Island in the Indian Ocean revealed that P. pacificus has invaded this island multiple times independently with different carrier beetles, resulting in this island harboring the complete worldwide diversity of P. pacificus haplotypes (Herrmann et al ., ; Morgan et al ., ). Indeed, the population structure and evolutionary history of P. pacificus on La Réunion Island provided a paradigm for detailed studies of the nematodes´ adaptations to new environments (McGaughran et al ., ; 2014; ; Morgan et al ., ; Moreno et al ., ). Among several P. pacificus hosts on La Réunion, the endemic rhinoceros beetle Oryctes borbonicus represents an interesting study system because more than 90% of beetle individuals harbor P. pacificus dauer larvae (Morgan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory behavior has also been studied in Pristionchus pacificus , a necromenic species that associates with beetles [87]. Necromenic nematodes do not kill their hosts, but rather wait for their hosts to die and then propagate on the host cadaver.…”
Section: Introductionmentioning
confidence: 99%
“…As such, necromeny is often considered an evolutionary intermediate between free-living and parasitic life styles. P. pacificus is attracted to live beetles as well as beetle odorants, beetle pheromone, and plant odorants [87,88]. Olfactory preferences differ among wild P. pacificus strains and among closely related Pristionchus species, perhaps reflecting differences in their host preferences [87,88].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation